Cost-effectiveness analysis of simeprevir in combination with peginterferon and ribavirin for treatment-naïve chronic hepatitis C genotype 1 patients in Japan. (July 2015) - Kuwabara, Hiroyo; Westerhout, Kirsten; Treur, Maarten; Cerri, Karin; Mahlich, Joerg; Yatsuhashi, Hiroshi
Abstract Aim: Simeprevir (SMV), a protease inhibitor, recently became available for the treatment of chronic hepatitis C (HCV) genotype 1 patients in Japan. The introduction of triple therapy using SMV in combination with peginterferon and ribavirin (PR) significantly improves the cure rate. The aim was to assess the cost-effectiveness of SMV with PR (SMV/PR) compared to telaprevir with PR (TVR/PR), PR alone, or no treatment in treatment-naïve patients in Japan. Methods: A Markov model was developed to reflect the natural disease progression of HCV and to estimate the average life years and lifetime healthcare costs per patient. Sustained virologic response rates were obtained from a network meta-analysis including randomized clinical trials conducted in Japan. Patient baseline characteristics, HCV progression rates, mortality, medical resource utilization, and unit costs were obtained from Japanese sources. Outcomes were reported as incremental cost-effectiveness ratios as well as incremental cost and life years. Various sensitivity analyses were conducted to assess the uncertainty around model outcomes. Results: SMV/PR was estimated to be a cost-effective treatment option as more life years were gained by 0.235 and 0.873 years at a reduced cost by ¥263, 037 and ¥776, 900 compared to TVR/PR and PR alone, respectively. The results were robust to sensitivity analyses, in particular in the comparison of SMV/PR with PR alone. The multivariate probabilistic sensitivity analyses showed that the probability of SMV/PR being cost-effective was relatively constant at ∼87% at any willingness to pay. Conclusions: SMV/PR is estimated to be the most cost-effective treatment strategy for treatment-naïve HCV genotype 1 patients in Japan.